2020
DOI: 10.3389/fcell.2020.575223
|View full text |Cite
|
Sign up to set email alerts
|

Subversion of Ras Small GTPases in Cutaneous Melanoma Aggressiveness

Abstract: The rising incidence and mortality rate associated with the metastatic ability of cutaneous melanoma represent a major public health concern. Cutaneous melanoma is one of the most invasive human cancers, but the molecular mechanisms are poorly understood. Moreover, currently available therapies are not efficient in avoiding melanoma lethality. In this context, new biomarkers of prognosis, metastasis, and response to therapy are necessary to better predict the disease outcome. Additionally, the knowledge about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 163 publications
(253 reference statements)
0
8
0
Order By: Relevance
“…Despite the remarkable efforts to improve our understanding of CM biology, there is still a need to identify new biomarkers to further stratify patients based on prognosis, metastatic propensity, and response to therapy [15]. Unfortunately, current knowledge about ARF family members in CM is limited, and in particular, ARL proteins' involvement in CM etiology and progression remains unknown [26]. Hence, we evaluated the effect of ARL expression in prognosis, immune microenvironment modification, and their functional interactions with well-established signaling pathways in CM by performing an integrative analysis of open access databases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the remarkable efforts to improve our understanding of CM biology, there is still a need to identify new biomarkers to further stratify patients based on prognosis, metastatic propensity, and response to therapy [15]. Unfortunately, current knowledge about ARF family members in CM is limited, and in particular, ARL proteins' involvement in CM etiology and progression remains unknown [26]. Hence, we evaluated the effect of ARL expression in prognosis, immune microenvironment modification, and their functional interactions with well-established signaling pathways in CM by performing an integrative analysis of open access databases.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Arf proteins, the biochemical and functional characterization of Arls under physiological and pathological conditions is poorly explored [26]. The physiological functions of most Arls are still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current immunotherapies for advanced stage melanomas involve antagonization of cytotoxic T-lymphocyte-associated protein-4 (CTLA-4, ipilimumab) and programmed cell death protein-1 (PD-1, nivolumab and pembrolizumab), but in 45-70% of cases these therapies encounter primary resistance ( Table 1 ) ( 5 , 11 ). Further, immunotherapies with initially promising responses eventually yield to cancer progression in ~20-30% of respondents as secondary resistance occurs ( 5 , 13 , 14 ). Moreover, relatively high recurrence rates persist among patients treated with immunotherapies and the 5-year survival rate for advanced melanoma rests around 40% ( 1 , 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…GTP-binding proteins serve as molecular switches in cell signaling pathways . Aberrant expression and/or activities of GTP-binding proteins, including small GTPases, are known to be associated with melanoma metastasis. , Huang et al reported a targeted proteomic method combining stable isotope labeling by amino acids in cell culture (SILAC), sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis (PAGE) fractionation, and multiple-reaction monitoring (MRM) analysis, to quantify small GTPases in matched pairs of primary/metastatic melanoma cells. Based on liquid chromatography (LC)–mass spectrometry (MS)/MS and bioinformatic analysis, they revealed a potential role of RAB38 in enhancing melanoma metastasis through the upregulation of matrix metalloproteinase 2 (MMP2) and MMP9.…”
Section: Introductionmentioning
confidence: 99%